225 First Contact: A Series of Zoom-Based, Virtual on Call Shifts. (28th February 2022) - Choi, B.; Fu, H.; Ogunmwonyi, I.; Gargan, K.
Abstract: Aim: COVID-19 has resulted in reduced exposure to on-call shifts where medical students could increase confidence and proficiency in task prioritisation and decision making. Existing 'simulated on-calls' provide a substitute in a controlled environment, however in person teaching has also been limited by COVID-19. Our virtual on-call sessions use ZOOM to replicate the higher-level learning experiences normally conferred by live simulation. Method: We designed a series of virtual 'on-calls' for medical students. Participants were 'on-call', receiving 'bleeps' which were 'answered' by calling a facilitator via ZOOM. The facilitator would roleplay a scenario and the 'Electronic Patient Record' (EPR) on Google Forms contained patient notes and observations. Students needed to collect information from the facilitator and document a management plan into the EPR. Participants received 'bleeps' of varying complexity, urgency and relevance and were expected to prioritise and triage tasks accordingly. Evaluation was via a pre/post session quiz with separate feedback forms. Results: 23 students from 18 universities participated. Students reported increased confidence in managing on-call scenarios, and average scores improved in the post session quiz. Positive feedback was paid to the variety of scenarios, the EPR system and the feeling of realism elicited from the need to triage and prioritise jobs. Conclusions: Our framework uses readily accessible technology to provide interactive learning experience. Feedback suggested students engaged in higher order learning and thinking, achieving our stated aims. We aim to incorporate technologies such as automation software which will allow for a scalable, free, and accessible virtual on call.